2015
DOI: 10.1371/journal.pone.0130334
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Storage Lipids in the Relation between Fecundity, Locomotor Activity, and Lifespan of Drosophila melanogaster Longevity-Selected and Control Lines

Abstract: The contribution of insect fat body to multiple processes, such as development, metamorphosis, activity, and reproduction results in trade-offs between life history traits. In the present study, age-induced modulation of storage lipid composition in Drosophila melanogaster longevity-selected (L) and non-selected control (C) lines was studied and the correlation between total body fat mass and lifespan assessed. The trade-offs between fecundity, locomotor activity, and lifespan were re-evaluated from a lipid-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 82 publications
(108 reference statements)
1
10
0
Order By: Relevance
“…Future studies are needed to compare the nutrient intake of a range of host‐specialist species that also investigate how male reproductive effort is affected. Finally, it has been reported that lipid storage could play a role in the lifespan–reproduction trade‐off (Moghadam et al., 2015). Investigating lipid regulation and their effect on life‐history traits using the GF approach might be a next step to understand the link between aging mechanisms and the degree of specialization.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are needed to compare the nutrient intake of a range of host‐specialist species that also investigate how male reproductive effort is affected. Finally, it has been reported that lipid storage could play a role in the lifespan–reproduction trade‐off (Moghadam et al., 2015). Investigating lipid regulation and their effect on life‐history traits using the GF approach might be a next step to understand the link between aging mechanisms and the degree of specialization.…”
Section: Discussionmentioning
confidence: 99%
“…As many studies have indicated the increased fattening of insects in response to other stress‐induced conditions (Hansen et al., 2013; Moghadam et al., 2015; Piiroinen et al., 2014), we suggest that the increased body fat content in dung beetles from logged forests reinforces the use of this trait as a likely early warning biomarker to assess the environmental quality of disturbed tropical forests.…”
Section: Discussionmentioning
confidence: 99%
“…Reproduction is a high cost process (Hansen et al., 2013), and fat content is considered the currency (Barry & Wilder, 2013). Although not always observed (Flatt et al., 2008; Wilder, Raubenheimer, & Simpson, 2015), the link between reduced reproduction and increased fat storage has been demonstrated for many insects (Hansen et al., 2013; Moghadam et al., 2015; Wilder et al., 2015). Similarly, previous research has found a positive relationship between reduced fecundity, increased fattening, and higher starvation stress resistance (Broughton et al., 2005; Hansen et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6A). Although several studies have reported an interaction between lipid stores and longevity in animals [5459], the mechanisms underlying this effect are not well understood. In flies, genetic induction of β-oxidation rates increases the average lifespan [60].…”
Section: Discussionmentioning
confidence: 99%